(i,j) - Sc - Continuous and (i,j) - θSc - continuous Functions - KHALAF, ALIAS B.; Aziz, Hardi N.; Sharef, Hardi A. (Science Journal of University of Zakho, 2013)
In this paper, we introduce new types of continuity in bitopological spaces called (i,j) - Sc - continuous and (i,j) - θSc - continuous. We discuss the relationship between these types of continuity and other known types of continuous functions.